Pemanfaatan Peluang Pasar Produk Lokal Dalam Rangka Meningkatkan Ekonomi Masyarakat di Kabupaten Agam Sumatera Barat - Rita Youfa; Desniorita Desniorita; Radna Ningsih; Sri Elfina; Adlina Safitri Helmi; Oktrison Oktrison; Jerry Jerry (Journal of Industrial Community Empowerment, 2023)
The partners involved in this PKM activity are farming communities in Nagari Matur Mudik, Nagari Lawang and Nagari Tigo Balai Kec. Thanks, Kab. Agam is located to the north of Padang City, West Sumatra Province, which is ± 94 km from the Padang ATI Polytechnic Campus. Most of the people of Nagari Matur Mudik, Kec. Thanks, Kab. Agam has a livelihood as a farmer. The Community Partnership Program aims to increase the economic value of agricultural commodities in Nagari Matur Mudik, Nagari Lawang and Nagari Tigo Balai, Matur District, Agam Regency. Sales of agricultural raw materials are considered to be still constrained in the distribution/sales process which is only limited to traditional markets. Efforts are being made through the processing of agricultural raw materials into delicious and nutritious products, as well as having competent selling points in the market. The methods used in this program are counseling and training methods. This program works with the PKK team and the farming community as partners in the center for processing agricultural products into food products for the trading community. The flow of activities includes the preparatory stage in the form of observations to related offices/agencies. Then the implementation stage, namely counseling and training for the community in Matur District, which is centered at the Nagari Matur Mudik Village office, Nagari Lawang and Nagari Tigo Balai. With direct participation by the community, it is hoped that new and creative ideas will emerge by the community in processing agricultural products so that this program can be sustainable as a concrete effort to continue to improve the economy of the local community.